THE EFFECTIVENESS AND EFFICIENCY OF BLENDED LEARNING AT SPORT SCHOOLS IN INDONESIA - Adi, Sapto; Fathoni, Abi Fajar (International Journal of Psychosocial Rehabilitation, 2020)
Students in sport schools find it difficult to attend face-to-face learning in class with their teacher. It is because students in sport schools are athletes who often leave the classroom to do training camps or to take part in competitions outside the city for a long time. Blended-learning-based learning can be a solution because this learning can be done anywhere and anytime. The purpose of this study was to look at the effectiveness and efficiency of blended learning-based learning in sport schools. The research method used was an experiment with The One Group Pre-test Post-test design. The data showed that after the blended-learning-based learning, the students’ learning outcomes increased and the students were able to understand the material in relatively short time. Thus, blended-learning-based learning was effective and efficient to be used in sport schools.